Digitoxin: overdose in pharmaceutical compounded preparation - Yano, Helena Miyoco (2005)
The authors report a case on an inaccurate pharmacy compounding of digitoxin compounded preparation, which revealed an amount of 565% of active digitoxin in reference to that concentration stated in the label. The preparation analysis request was sent with a clinical record and sanitary authority notification on severe digitalic intoxication symptoms presented by the patient after taking that medication. The reported episode points up the lack of quality control at compounding pharmacies during dispensing drugs and compounds, with narrow therapeutic indices as digitalis drug preparations.